The Influence of Tax Planning, Profitability, And Costs Operations For Earning Management - Chris Monica Levia; Ickhsanto Wahyudi (Best Journal of Administration and Management, 2025)
This study aims to analyze the influence of tax planning, profitability, and operational efficiency (measured by BOPO—Biaya Operasional Pendapatan Operasional) on earnings management in Indonesian public companies. Using regression analysis on data from 90 company observations listed on the Indonesia Stock Exchange (BEI) between 2019 and 2021, the research reveals several key findings. Tax planning, measured by the Effective Tax Rate (ETR), does not significantly affect earnings management, indicating that tax obligations do not directly drive managerial decisions to manipulate financial reports. Similarly, profitability, measured by Return on Assets (ROA), shows no significant impact on earnings management, suggesting that neither high nor low profitability consistently leads to increased earnings manipulation. In contrast, BOPO demonstrates a positive and statistically significant effect on earnings management, highlighting that operational cost management is a critical lever used by firms to influence reported earnings. This implies that companies may manipulate operational expenses to present more favorable financial outcomes. Overall, the independent variables explain only about 28% of the variation in earnings management practices, indicating that other unexamined factors also play a crucial role. The results suggest that regulators should pay closer attention to how operational costs are managed and reported, as they can be indicators of potential earnings manipulation. Future research could expand on these findings by incorporating additional variables such as corporate governance, audit quality, and institutional factors, as well as employing qualitative methods to gain deeper insights into earnings management practices.